Research methods in psychology - Breakwell, Glynis M. (Glynis Marie); Smith, Jonathan A.; Wright, Daniel B. (Los Angeles : SAGE, 2012)
"Research Methods in Psychology has been substantially and meticulously revised in its Fourth Edition. Continuing to offer enviable coverage of the research methods that psychology students at intermediate levels need to muster, the textbook has now been broadened to cover the full suite of beginner level research methods too. It now has extensive coverage of psychological methods, both quantitative and qualitative. For this new edition, a new editorial arrangement has been put into place. Daniel B. Wright steps in to help steer the quantitative research methods section of the textbook and partners Jonathan A. Smith who remains as the lead Editor for qualitative research methods. Glynis M. Breakwell, as with all editions to-date, remains as overseeing Editor for the textbook. Together, they have brought together a team of world leading educators in psychological methods to write accessible and engaging chapters that help students not only learn about the central methods for psychological investigation today, but to see the 'real world' value and importance of using methods well for very good research. As a result, all parties involved have shaped this new edition into a tour-de-force undergraduate textbook."--Publisher's website.
Part 1: Introduction. Research Questions and Planning Research / Glynis M. Breakwell, Daniel B. Wright and Jonathan A. Smith. -- Part 2: Quantitative research: data collection and analysis. Introduction to Quantitative Research / Chris Fife Schaw ; Experimental Method / Graham Hole ; Quasi-Experimental Design / Chris Fife-Schaw ; Surveys and Sampling / Patrick Sturgis ; Questionnaire Design / Chris Fife-Schaw ; Psychometrics / John Rust ; Descriptive Statistics / Marianna E. Carlucci and Daniel B. Wright ; Graphical and Numerical Methods ; Inferential Statistics / Marianna E. Carlucci and Daniel B. Wright ; Factorial ANOVA / Katherine McGuire and Kamala London ; Correlation and Regression / Jeremy Miles ; Exploratory Factor Analysis / Daniel B. Wright and Daniella K. Villalba. -- Part 3: Qualitative research: data collection and analysis. Introduction to Qualitative Methods / Virginia Eatough ; Observational Methods / Rudi Dallos ; Interviewing / Glynis M. Breakwell ; Diary and Narrative Methods / Glynis M. Breakwell ; Focus Groups / Lynne Millward ; Interpretative Phenomenological Analysis / Jonathan A. Smith and Virginia Eatough ; Grounded Theory / Karen Henwood and Nick Pidgeon ; Discourse Analysis / Adrian Coyle ; Content Analysis / Glynis M. Breakwell. -- Part 4: Writing up your research. What if Victor Had Used the APA Manual to Write up His Research? / Daniel B. Wright, Jonathan A. Smith and Glynis M. Breakwell.
Includes bibliographical references (p. [563]-584) and index.
Keywords: Psychology -- Research; Psychology -- Methodology; Psychology; Research -- methods; Research Design